Formation Processes of Nanocomposite Strengthening Particles in Rapidly Quenched Al-Sc-Zr Alloys - A.V. Kotko; V.K. Nosenko; O.A. Molebny; T.O. Monastyrska; A.L. Berezina (Журнал нано- та електронної фізики)
Decomposition processes of supersaturated solid solution of aluminium alloys alloyed with Sc and Zr have been studied in the work. The binary hypereutectic Al-Sc alloys, hyperperitectic Al-Zr alloys and ternary Al-Sc-Zr alloys were chosen. Alloys were obtained by the melt-spinning. Melts were quenched from temperatures of Т = 1000 C and Т = 1400 ºC. The study of the structure of rapidly solidifyed binary Al alloys alloyed with Sc and Zr showed that the crystallization of anomalously supersaturated solid solution (Tquen. = 1400 ºC) or the crystallization with the formation of "fan" structure (Tquen. = 1000 ºC) are possible depending on the quenching temperature of the melt. The decomposition of anomalously supersaturated solid solution is continuous, with the precipitation of nano-sized spherical Al3X (X-Sc, Zr) particles of L12-ordered phase which is isomorphous to matrix. It was found that the loss of thermal stability of Al-Sc alloys is due to the loss of coherence of the strengthening Al3Sc phase. In Al-Zr alloys the loss of strength is due to the formation of a stable tetragonal DO23-ordered A13Zr phase. After co-alloying of Al by Sc and Zr a bimodal grained structure was observed for the hypereutectic ternary alloy (Tquen. = 400ºC). Nano-sized grains of 50-60 nm were present on the boundaries of 1-2 µm large-sized grains. TEM shows the formation of nanocomposite Al3Zr/Al3Sc particles. The formation of Al3Zr shell changes the nature of the interfacial fit of the particle with the matrix and slows down the decomposition during the coalescence. Ternary Al-Sc-Zr alloys have significantly higher thermal stability during aging as compared to binary Al-Sc and Al-Zr alloys. Decomposition processes of supersaturated solid solution of aluminium alloys alloyed with Sc and Zr have been studied in the work. The binary hypereutectic Al-Sc alloys, hyperperitectic Al-Zr alloys and ternary Al-Sc-Zr alloys were chosen. Alloys were obtained by the melt-spinning. Melts were quenched from temperatures of Т = 1000 ºC and Т = 1400 ºC. The study of the structure of rapidly solidifyed binary Al alloys alloyed with Sc and Zr showed that the crystallization of anomalously supersaturated solid solution (Tquen. = 1400 ºC) or the crystallization with the formation of "fan" structure (Tquen. = 1000 ºC) are possible depending on the quenching temperature of the melt. The decomposition of anomalously supersaturated solid solution is continuous, with the precipitation of nano-sized spherical Al3X (X-Sc, Zr) particles of L12-ordered phase which is isomorphous to matrix. It was found that the loss of thermal stability of Al-Sc alloys is due to the loss of coherence of the strengthening Al3Sc phase. In Al-Zr alloys the loss of strength is due to the formation of a stable tetragonal DO23-ordered A13Zr phase. After co-alloying of Al by Sc and Zr a bimodal grained structure was observed for the hypereutectic ternary alloy (Tquen. = 400ºC). Nano-sized grains of 50-60 nm were present on the boundaries of 1-2 µm large-sized grains. TEM shows the formation of nanocomposite Al3Zr/Al3Sc particles. The formation of Al3Zr shell changes the nature of the interfacial fit of the particle with the matrix and slows down the decomposition during the coalescence. Ternary Al-Sc-Zr alloys have significantly higher thermal stability during aging as compared to binary Al-Sc and Al-Zr alloys. Decomposition processes of supersaturated solid solution of aluminium alloys alloyed with Sc and Zr have been studied in the work. The binary hypereutectic Al-Sc alloys, hyperperitectic Al-Zr alloys and ternary Al-Sc-Zr alloys were chosen. Alloys were obtained by the melt-spinning. Melts were quenched from temperatures of Т = 1000 C and Т = 1400 ºC. The study of the structure of rapidly solidifyed binary Al alloys alloyed with Sc and Zr showed that the crystallization of anomalously supersaturated solid solution (Tquen. = 1400 ºC) or the crystallization with the formation of "fan" structure (Tquen. = 1000 ºC) are possible depending on the quenching temperature of the melt. The decomposition of anomalously supersaturated solid solution is continuous, with the precipitation of nano-sized spherical Al3X (X-Sc, Zr) particles of L12-ordered phase which is isomorphous to matrix. It was found that the loss of thermal stability of Al-Sc alloys is due to the loss of coherence of the strengthening Al3Sc phase. In Al-Zr alloys the loss of strength is due to the formation of a stable tetragonal DO23-ordered A13Zr phase. After co-alloying of Al by Sc and Zr a bimodal grained structure was observed for the hypereutectic ternary alloy (Tquen. = 400ºC). Nano-sized grains of 50-60 nm were present on the boundaries of 1-2 µm large-sized grains. TEM shows the formation of nanocomposite Al3Zr/Al3Sc particles. The formation of Al3Zr shell changes the nature of the interfacial fit of the particle with the matrix and slows down the decomposition during the coalescence. Ternary Al-Sc-Zr alloys have significantly higher thermal stability during aging as compared to binary Al-Sc and Al-Zr alloys.